2019
DOI: 10.1371/journal.pone.0220535
|View full text |Cite
|
Sign up to set email alerts
|

Changes in visual function and retinal structure in the progression of Alzheimer's disease

Abstract: Background Alzheimer’s Disease (AD) can cause degeneration in the retina and optic nerve either directly, as a result of amyloid beta deposits, or secondarily, as a result of the degradation of the visual cortex. These effects raise the possibility that tracking ophthalmologic changes in the retina can be used to assess neurodegeneration in AD. This study aimed to detect retinal changes and associated functional changes in three groups of patients consisting of AD patients with mild disease, AD pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
86
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(98 citation statements)
references
References 98 publications
9
86
0
3
Order By: Relevance
“…Cell displacement and process reorientation towards an injury site are early features of microglial activation [44,45]. The microglial soma displacement towards the nuclear layers could explain the thickening in some areas of the retinal nuclear layers and the parallel thinning in plexiform layers observed by OCT using a new method for the segmentation of retinal layers in patients with mild AD [11,46]. In addition, it has been postulated that the vertical arrangement of microglial cells, like that of Müller cells, could assist in the distribution of signaling between different microglial plexuses to communicate to the rest of the retina where damage has occurred [6,47].…”
Section: Discussionmentioning
confidence: 99%
“…Cell displacement and process reorientation towards an injury site are early features of microglial activation [44,45]. The microglial soma displacement towards the nuclear layers could explain the thickening in some areas of the retinal nuclear layers and the parallel thinning in plexiform layers observed by OCT using a new method for the segmentation of retinal layers in patients with mild AD [11,46]. In addition, it has been postulated that the vertical arrangement of microglial cells, like that of Müller cells, could assist in the distribution of signaling between different microglial plexuses to communicate to the rest of the retina where damage has occurred [6,47].…”
Section: Discussionmentioning
confidence: 99%
“…These changes, which were reported in previous studies, suggested that changes in the RNFL thickness could be used as an early marker of AD-related brain atrophy [ 27 , 36 ]. In addition, a decrease in pRNFL thickness has been correlated with impaired cognition during disease progression [ 37 , 38 , 39 , 40 ]. This pRNFL decrease was confirmed as a potential biomarker for predicting cognitive decline in older adults during preclinical dementia [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with established AD, a reduction in mRNFL thickness has been demonstrated in different sectors [ 37 , 41 , 42 , 43 ]. The difference between the inclusion criteria of these patients, in relation to the MMSE, makes the classification of the different stages of AD not equivalent.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have analysed that superior macular damage tends to combine the visual field defect closer to fixation 13,30 . Some studies have reported that Alzheimer's disease is related to the optic nerve and the inner layers of the central macular area damages [31][32][33] . However, we excluded patients with Alzheimer's disease and other neurodegenerative diseases like cognitive decline and sensorineural hearing loss from this study in order to eliminate potential bias.…”
Section: Discussionmentioning
confidence: 99%